Genetic relatedness of Tunisian Sign Language and French Sign Language - Nefaa, Aymen (Frontiers in Communication, 2023)
This article constitutes the first cognate study aiming at the verification of the genetic link between LSF (French Sign Language) and LST (Tunisian Sign Language) through a lexicostatistical analysis of both sign languages (SLs). To do this, an orthographic/graphic version of Woodward's (1987) 100 basic lexical items list was utilized to elicit LST lexical items from 61 Tunisian deaf signers with a mean age of 20.86 from three different governorates in the country (Tunis, Nabeul, and Douz). The lists were then compared to LSF lexical signs from two LSF dictionaries (Elix and IVT) using ELAN 6.2 annotation software.Results of the lexicostatistical analysis between the varieties of LST in the three governorates and LSF suggest a proposed distant genetic relationship between the two SLs.